Implementasi Strategi Pendekatan Kinestetik Melalui Ice Breaking pada Bimbingan Belajar Bahasa Inggris oleh Mahasiswa KKN UNP untuk Anak di Desa Kubang Utara Sikabu, Kecamatan Lembah Segar, Kota Sawahlunto - Sandra Dewi; Ghina Fitri Tampubolon; Haifa Najla Amri; Lathifa Asma Hayati; Asri Rozak (GLOBAL SCIENTS PUBLISHER, 2025)
The Community Service Program (KKN) of Universitas Negeri Padang plays a key role in supporting higher education to meet community needs. One implemented program was English tutoring for children in Kubang Utara Sikabu Village. The activity took place over four days with six meetings. The method used was a kinesthetic approach with ice-breaking activities aimed at boosting children’s engagement in learning. Data were collected by directly observing students’ participation and responses during the activities. The results showed that ice-breaking activities based on a kinesthetic approach effectively increased children’s participation, motivation, and enthusiasm for learning English. This approach also created a more enjoyable and interactive learning environment, which is especially helpful for young learners in rural areas. Therefore, using kinesthetic strategies through ice-breaking activities can be an effective way to improve children’s involvement and interest in English learning during community-based educational programs.